MIS-C: A COVID-19-as sociated condition between hypoimmunity and hyperimmunity - Gelzo, Monica; Castaldo, Alice; Giannattasio, Antonietta; Scalia, Giulia; Raia, Maddalena; Esposito, Maria Valeria; Maglione, Marco; Muzzica, Stefania; D’Anna, Carolina; Grieco, Michela; Tipo, Vincenzo; La Cava, Antonio; et al. (Frontiers in Immunology, 2022)
Multisystem inflammatory syndrome in children (MIS-C) is a rare, severe complication of COVID-19. A better knowledge of immunological, cellular, and genetic characteristics of MIS-C could help better understand the pathogenesis of the disease and contribute to identifying specific diagnostic biomarkers and develop targeted therapies. We studied 37 MIS-C children at hospital admission and 24 healthy controls analyzing serum cytokines (IFN-, IFN-β, IFN-γ, IL-6, IL-10, IL-17A, IL-12p70 and TNF), lymphocyte populations by flow cytometry and 386 genes related to autoimmune diseases, autoinflammation and primary immunodeficiencies by NGS. MIS-C patients showed a significant increase of serum IFN (despite a significant reduction of activated Th1) and ILs, even if with a great heterogeneity among patients, revealing different pathways involved in MIS-C pathogenesis and suggesting that serum cytokines at admission may help to select the inflammatory pathways to target in each patient. Flow cytometry demonstrated a relevant reduction of T populations while the percentage of B cell was increased in agreement with an autoimmune pathogenesis of MIS-C. Genetic analysis identified variants in 34 genes and 83.3% of patients had at least one gene variant. Among these, 9 were mutated in more patients. Most genes are related to autoimmune diseases like ATM, NCF1, MCM4, FCN3, and DOCK8 or to autoinflammatory diseases associated to the release of IFN like PRF1, NOD2, and MEF. Thus, an incomplete clearance of the Sars-CoV2 during the acute phase may induce tissue damage and self-antigen exposure and genetic variants can predispose to hyper-reactive immune dysregulation events of MIS-C-syndrome. Type II IFN activation and cytokine responses (mainly IL-6 and IL-10) may cause a cytokine storm in some patients with a more severe acute phase of the disease, lymphopenia and multisystemic organ involvement. The timely identification of such patients with an immunocytometric panel might be critical for targeted therapeutic management.